NURSING ASSISTANCE IN HYPERTENSIVE SYNDROMES IN GESTURE: A LITERATURE REVIEW (CIPEEX, 2022)
INTRODUCTION: HYPERTENSIVE SPECIFIC SYNDROME OF THE GESTATION (SHEG) IS A DISEASE OF GREAT MORBIDITY AND MORTALITY IN PREGNANCY, AMONG THE GESTATIONAL HYPERTENSIVE SYNDROMES, SPECIAL ATTENTION SHOULD BE GIVEN TO PREECLAMPSIA THAT OCCURS AS A FORM ALONE OR ASSOCIATED WITH CHRONIC ARTERIAL HYPERTENSION, SINCE THEY ARE LINKED MATERNAL AND PERINATAL OUTCOMES. CHARACTERIZED BY ARTERIAL HYPERTENSION, PROTEINURIA AND / OR EDEMA, WITH A HIGH INCIDENCE RATE AND PREVALENCE IN BRAZIL. CONSIDERED A MAJOR PUBLIC HEALTH PROBLEM, IT IS IMPORTANT FOR THE HEALTH TEAM TO KNOW THE PREDISPOSING FACTORS FOR THIS PATHOLOGY, IN ORDER TO BE ABLE TO RECOGNIZE THE POSSIBILITY OF DEVELOPING IT AT ANY TIME DURING THE PRE-NATAL PERIOD (PN). PREVENTION, PROMOTION AND PROTECTION OF HEALTH OF THE BINOMIAL. OBJECTIVE: TO DESCRIBE NURSING CARE IN THE CARE OF PREGNANT WOMEN WITH SHEG. METHODOLOGY: INTEGRATIVE LITERATURE REVIEW OF ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND NURSING DATABASE (BDENF), IN THE PERIOD BETWEEN 2010-2016, IN THE PORTUGUESE LANGUAGE. FOR THE ANALYSIS OF THE DATA THE RECOMMENDATIONS OF MENDES ET AL. (2008), WHICH PROPOSES SIX STEPS FOR THE ELABORATION OF A GOOD, EFFECTIVE, PRECISE AND RELEVANT INTEGRATIVE REVIEW. RESULTS: TWELVE ARTICLES WERE INCLUDED IN THIS REVIEW. TWO CATEGORIES EMERGED: CONCEPTS, INCIDENCE, RISK FACTORS, SIGNS AND SYMPTOMS OF SHEG; AND NURSING CARE AT SHEG. THE SYSTEMATIZATION OF NURSING CARE FOR THIS TYPE OF PATIENT WAS A CHALLENGE, SINCE IT IS NECESSARY TO PROVIDE ASSISTANCE TO THE PATIENTS' SELF-CARE DEMANDS, LIMITED BY DEFICITS INHERENT TO THE CLINICAL PICTURE'S GRAVITY, AND AT THE SAME TIME TO STIMULATE THEIR INDEPENDENCE FOR SELF-CARE, PROMOTING AN EMANCIPATORY ASSISTANCE FOR THE GENERAL WELFARE OF THE BINOMIAL. CONCLUSION: THE ARTERIAL HYPERTENSION IN PREGNANT WOMEN, WHEN DETECTED, REQUIRES HEALTH PROFESSIONALS TO BETTER PREPARE AND TAKE PREVENTIVE ACTIONS, LEADING TO THE PRACTICAL AND THEORETICAL FIELD AN ASSISTANCE TO THE MATERNAL-FETAL BINOMIAL FOCUSED ON THE IMPORTANCE OF PREVENTION. NURSES HAVE TECHNICAL / SCIENTIFIC KNOWLEDGE TO RECOGNIZE THE SIGNS SUGGESTIVE OF SHEG AND ITS GUIDELINES TO PREVENT POOR PROGNOSIS ARE VERY IMPORTANT FOR THE PREGNANT WOMAN.
Keywords: High risk pregnancy. Gestational hypertension. Pregnancy-induced hypertension. Nursing care